GENERALIZED QUASI-COINCIDENCE IN FUZZY SUB-HYPERMODULES - Ameri, R.; Hedayati, H.; Norouzi, M. (Italian Journal of Pure and Applied Mathematics, 2013)
We consider a general form of the notion of quasi-coincidence of a fuzzy point with a fuzzy set. We introduce the notions of (∈, qk)-fuzzy sub-hypermodule and (∈, ∈ ∨qk)-fuzzy sub-hypermodule of a given hypermodule, and investigate several properties of these notions.